Improving Encarta Search Engine Performance by Mining User Logs - Ling, Charles X.; Gao, Jianfeng; Zhang, Huajie; Qian, Weining; Zhang, Hongjiang (International Journal of Pattern Recognition and Artificial Intelligence, 2002)
We propose a data-mining approach that produces generalized query patterns (with generalized keywords) from the raw user logs of the Microsoft Encarta search engine.